2005
DOI: 10.1038/emm.2005.76
|View full text |Cite
|
Sign up to set email alerts
|

Bis induces growth inhibition and differentiation of HL-60 cells via up-regulation of p27

Abstract: Bis (Bag-3, CAIR), a Bcl-2-interacting protein, promotes the anti-apoptotic activity of Bcl-2 and increased levels of Bis have been observed in several disease models. The involvement of Bcl-2 and some Bcl-2-binding proteins in differentiation has recently been reported. However, the relevance of Bis to cellular differentiation remains unknown. The findings herein show that Bis expression is up-regulated during the differentiation of HL-60 cells. To investigate the effect of Bis expression on differentiation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Indeed, it has previously been shown that BAG3 can physically associate with a number of proteins potentially involved in tumorigenesis (e.g., PLC-γ, Akt, Bcl-XL, HspB8) (12,13,43,44); however, no correlation between these interactions and the prosurvival effect of BAG3 has been provided. Similarly, although it has been clearly demonstrated that BAG3 can affect the levels and/or activity of a number of other proteins potentially involved in tumor transformation (e.g., p27, Rac1, the focal adhesion proteins FAK and paxillin, the matricellular signal regulator CCN1) (45)(46)(47)(48), neither a clear mechanism through which BAG3 regulates them nor a clear causative role of BAG3 antiapoptotic activity has been demonstrated. Clearly, we believe that some of these proteins may play a causative role in the mechanism of action of BAG3, together with the pathway elucidated in this paper, because it is likely that BAG3 interacts with and regulates a number of different proteins through its multiple protein-binding domains.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has previously been shown that BAG3 can physically associate with a number of proteins potentially involved in tumorigenesis (e.g., PLC-γ, Akt, Bcl-XL, HspB8) (12,13,43,44); however, no correlation between these interactions and the prosurvival effect of BAG3 has been provided. Similarly, although it has been clearly demonstrated that BAG3 can affect the levels and/or activity of a number of other proteins potentially involved in tumor transformation (e.g., p27, Rac1, the focal adhesion proteins FAK and paxillin, the matricellular signal regulator CCN1) (45)(46)(47)(48), neither a clear mechanism through which BAG3 regulates them nor a clear causative role of BAG3 antiapoptotic activity has been demonstrated. Clearly, we believe that some of these proteins may play a causative role in the mechanism of action of BAG3, together with the pathway elucidated in this paper, because it is likely that BAG3 interacts with and regulates a number of different proteins through its multiple protein-binding domains.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of Bcl-2 decreasing with increasing grade and Hsp70 increasing was present in endometrioid histology of ovarian cancers (D), but not in serous tumors. (26,43,44). Cytoplasmic BAG-3 is a chaperone for Bcl-2 and Hsp proteins; in the nucleus, however, the function of BAG-3 has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of Bis promotes the differentiation of human promyelocytic cells and cell cycle arrest (32). Roles for Bis in cell adhesion and migration have been recently reported by separate groups, although their results differ: in one study overexpression of Bis is shown to inhibit the migration and adhesion of breast cancer cell lines, whereas in the other study bis-deficient fibroblasts have reduced motility and delayed formation of focal adhesion complex (12,14).…”
mentioning
confidence: 95%